The role of identity in the experiences of dementia care workers from a minority ethnic background during the COVID‐19 pandemic: A qualitative study - Mishca Hughes; Sarah Butchard; Clarissa Giebel (Wiley, 2023)
Abstract Background Care home staff working during the COVID‐19 pandemic experienced higher levels of stress and increased workloads. People from diverse ethnic backgrounds were disproportionately affected by the COVID‐19 pandemic. This study explored the identity experiences of care home staff from diverse ethnic backgrounds in the context of working during the COVID‐19 pandemic. Methods Fourteen semistructured interviews were conducted between May 2021 and April 2022 with ethnic minority care home staff in England, who worked during the pandemic. Participants were recruited using convenience and theoretical sampling. Interviews were conducted via telephone or online platforms. A social constructivist grounded theory methodology was utilised in analysing the data. Findings Participants described five key processes which facilitated or hindered the impact that their experiences had on their identity: dealing with uncertainty and transitioning into a COVID‐19 world; difficult emotions; experiences of discrimination and racism; the response from the care home and societal systems; and the personal vs collective responsibility. When participants' physical and psychological needs went unmet by support structures within the care home and/or society, they experienced a sense of injustice, lack of control and being unvalued or discriminated against by others. Conclusions This study highlights the importance of recognising the unique needs of staff from diverse ethnic backgrounds working in care homes and adapting working practices to improve impact on identity, job satisfaction and staff retention. Patient and Public Involvement One care home worker was involved in developing the topic guide and helping to interpret the findings.